Status Epilepticus Manifested as Continuous Epileptic Spasms - Liao, Jianxiang; Huang, Tieshuan; Srour, Myriam; Xiao, Yuhan; Chen, Yan; Lin, Sufang; Chen, Li; Hu, Yan; Men, Lina; Wen, Jialun; Li, Bing; Wen, Feiqiu; et al. (Frontiers in Neurology, 2020)
Objective: The etiology and outcome of status epilepticus with continuous epileptic spasms has not been clearly specified, and only rare cases have been reported in the literature. Here, we described 11 children with various etiology and different outcome who manifested continuous epileptic spasms. Methods: This is a cohort study designed to review the charts, video electroencephalography, magnetic resonance images, follow-up and outcomes of patients who present continuous epileptic spasms lasting more than 30 minutes. Results: Median age at onset was two years, range 2 months to 5.6 years. The etiology of continuous epileptic spasms for these 11 cases consisted of not only the traditional electro-clinical epilepsy syndromes with known or unknown etiology like West syndrome or Ohtahara syndrome, but also acute symptomatic etiology such as encephalitis, encephalopathy, which expanded the etiology spectrum of continuous spasms. The epileptic spasms were prolonged, lasting for a median 13.00 days (95% CI was 7.26-128.22 days). Interictal findings typically consisted of hypsarrhythmia or its variants, including burst suppression. Hospital stay was longer in acute symptomatic causes of continuous (59.67±50.82 with disturbance of consciousness vs 15±1.41days ) spasms. The long-term outcome was extremely poor in patients with defined electro-clinical epilepsy syndrome ,including severe motor and intellectual developmental deficits (follow-up 4.94±1.56 years) despite early identification and treatment. Epileptic spasms were refractory to corticosteroids, immuno-modulation or immunosuppressive therapies, and ketogenic diet. Conclusion: Continuous epileptic spasms with a variety of etiologies as a form of status epilepticus should be included into the international classification of status epilepticus, and as a rule result in severe brain impairments in patients with electro-clinical syndromes, and long hospital stay in patients with acute symptomatic causes. Further investigations are required for exploring effective treatment to improve outcomes.